Effect of experimental and clinical pain on the spatial distribution of muscle activity: a systematic review and meta-analysis - Mendez-Rebolledo, Guillermo; Orozco-Chavez, Ignacio; Salazar-Méndez, Joaquín; Morales-Verdugo, Juan; Martinez-Valdes, Eduardo (Frontiers in Human Neuroscience, 2025)
IntroductionMusculoskeletal dysfunctions can significantly impair quality of life due to persistent pain and neuromuscular adaptations. While regional activation patterns in healthy muscles are well-documented, the effects of clinical and experimental pain on these patterns remain inconsistent. Accordingly, this study systematically evaluates the scientific evidence on alterations in the spatial distribution of muscle activity, quantified by shifts in the center of activity of high-density surface electromyography (HD-sEMG) signals, under experimental and clinical pain conditions.MethodsA comprehensive database search was conducted from inception to June 6, 2025. The review included studies that evaluated the spatial distribution of muscle activity with HD-sEMG, analyzing two-dimensional shifts in the center of activity among individuals with clinical or experimentally induced pain. Methodological quality was assessed using the adapted Newcastle-Ottawa Scale, and evidence certainty was evaluated with the GRADE approach. A random-effects model was employed in the meta-analysis to account for variability across studies.ResultsTwenty studies involving 562 participants (231 control, 266 clinical pain, and 65 experimental pain) were included. The meta-analysis revealed a statistically significant shift in the center of activity in individuals with clinical pain compared with asymptomatic controls (SMD = 0.49; 95% CI = 0.15 to 1.84; p = 0.004), particularly those with chronic low back pain, with a low effect size (SMD = 0.43; 95% CI = 0.03 to 0.83; p = 0.04), indicating altered spatial distribution of muscle activity. A meta-analysis for experimental pain was not feasible due to limited data.ConclusionsThese findings underscore that clinical pain is associated with altered spatial distribution of muscle activity and emphasize the need for standardized methodologies and further research across diverse populations to enhance pain management and rehabilitation strategies.Systematic review registrationThis study was prospectively registered in the International Prospective Register of Systematic Reviews (PROSPERO) (identifier CRD42024534320), https://www.crd.york.ac.uk/PROSPERO/view/CRD42024534320.